Crisp1 and alopecia areata in C3H/HeJ mice - Sundberg, John P. (2014)
Alopecia areata (AA), a cell mediated autoimmune disease, is the second most common form of hair loss in humans. While the autoimmune disease is responsible for the underlying pathogenesis, the alopecia phenotype is ultimately due to hair shaft fragility and breakage associated with structural deficits. Quantitative trait genetic analyses using the C3H/HeJ mouse AA model identified cysteine-rich secretory protein 1 (Crisp1), a hair shaft structural protein, as a candidate gene within the major AA locus. Crisp1 transcripts in the skin at various times during disease development were barely detectable. In situ hybridization identified Crisp1 expression within the medulla of hair shafts from clinically normal strains of mice but not C3H/HeJ mice with AA. Follow-up work with 5-day-old C3H/HeJ mice with normal hair also had essentially no expression of Crisp1. Other non-inflammatory based follicular dystrophy mouse models with similar hair shaft abnormalities also have little or no Crisp1 expression. Shotgun proteomics, used to determine strain difference in hair proteins, confirmed that there was very little CRISP1 within normal C3H/HeJ mouse hair in comparison to 11 other strains. However, mutant mice with hair medulla defects also had undetectable levels of CRISP1 in their hair. Crisp1 null mice had normal skin, hair follicles, and hair shafts indicating that the lack of the CRISP1 protein does not translate directly into defects in the hair shaft or hair follicle. These results suggest that CRISP1 may be an important structural component of mouse hair and that its strain-specific dysregulation may indicate a predisposition to hair shaft disease such as AA.